2014
DOI: 10.1177/0042098014561723
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the importance of the strategy used to identify gentrification

Abstract: Urban scholars have described the importance of gentrification in major cities across the USA since the 1970s. While there is consensus that gentrification shaped social and physical aspects of neighbourhoods, scholars have yet to agree on how gentrified neighbourhoods should be identified. Owing to the lack of consensus, gentrification was measured in a variety of ways, which greatly influenced the neighbourhoods studied in previous research and potentially the findings of research that assessed the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 23 publications
2
125
0
Order By: Relevance
“…While this study used an empirically tested measure of gentrification, other measures may yield different results. 1 Future research should explore the relation of SRH with other gentrification measures. In addition, our analysis should be replicated in other regions of the USA, as well as internationally, to determine how the effects of gentrification vary based on local character.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study used an empirically tested measure of gentrification, other measures may yield different results. 1 Future research should explore the relation of SRH with other gentrification measures. In addition, our analysis should be replicated in other regions of the USA, as well as internationally, to determine how the effects of gentrification vary based on local character.…”
Section: Resultsmentioning
confidence: 99%
“…A fundamental problem in the existing debate is the inconsistent fashion in which gentrified neighborhoods were identified. 1 We draw on a recently developed typology which emphasizes the increasing exclusivity of neighborhoods as a result of socioeconomic change, 4 adding to it the distinction of racial change brought about by this gentrification. We use hierarchical linear modeling to determine the implications of gentrification for self-rated health (SRH).…”
Section: Introductionmentioning
confidence: 99%
“…Owens (2012) found that socioeconomic ascent based on census-based indicators commonly employed to identify gentrification captures various forms of neighborhood change, many of which are not inherent to the direct indicators of neighborhood upgrading associated with gentrification. Moreover, Barton (2014) demonstrated that Bostic and Martin's (2003) and Freeman's (2005) census-based strategies identify gentrification in distinct areas from both each other and well-known gentrifying areas identified in newspaper content. Wyly and Hammel (1999) also found that tracts that they identified as gentrifying correlated with expected socioeconomic census variables, but approximately 10 % of tracts were also incorrectly classified as gentrifying when using the same census variables to identify gentrification.…”
Section: Methodsmentioning
confidence: 99%
“…While a national-level analysis can shed light on general patterns, measuring gentrification, particularly by applying uniform criteria to capture socioeconomic ascent in neighborhoods across cities, often does not necessarily identify areas associated with gentrification or undergoing similar types of change (Owens, 2012; Barton, 2016). Because we have a large enough sample size to examine residential mobility patterns for various subpopulations and across various types of neighborhoods within a single city, we therefore focus on a single city in this study.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%